FANTASMA_B: intelligere (or I know I have a somewhat stupid way of being) - Sabino, Isabel (Farol, 2026)
Eternal questions hover over art, artistic creation, and painting—questions regarding their definition, place, necessity, function, and more—that resurface like recurring specters even when they seem resolved. This essay explores the phantom that the *cosa mentale* (according to Leonardo, Francisco de Holanda, and others) has always implied within the paradoxical materiality of painting and art in general. Is it, after all, base matter like paint, or is it idea—pure spirit? This, in turn, draws the intelligence-stupidity dichotomy into the context of the natural-artificial debate. For does not the phantom of human stupidity hover over artificial intelligence, just as it does over all materiality that gives form to ideas? Thus, let us speak of phantoms through film, music, and—especially—art and painting, inquiring into their wisdom.